Genomic constitution of Festuca × Lolium hybrids revealed by the DArTFest array - Kopecký, David; Bartoš, Jan; Christelová, Pavla; Cernoch, Vladimír; Kilian, Andrzej; Doležel, Jaroslav (TAG. Theoretical and applied genetics. Theoretische und angewandte Genetik, 2011)
Complementary attributes of Festuca and Lolium grasses can be combined in hybrid cultivars called Festuloliums, which are becoming increasingly popular fodder crops and amenity plants. Genomic constitution of commercially available Festuloliums was reported to vary from almost equal representation of parental genomes to apparent lack of one of them based on molecular cytogenetic analyses and screening with a small set of DNA markers, both approaches with limited resolution. Here, we describe the use of the DArTFest array comprising 3,884 polymorphic DArT markers for characterization of genomes in five Festulolium cultivars. In any of the cultivars, the minimum number of informative markers, which discriminated the parental Lolium and Festuca genomes was 361 and 171, respectively. Using the DArTFest array, it was possible to determine hybrid genome constitution at resolution which has never been achieved before and the analysis of a set of randomly selected plants from each cultivar provided information on genetic structure of outcrossing Festulolium cultivars. In addition to a core set of markers typical for each hybrid cultivar, markers occurring at low frequency among the plants within each cultivar were identified. Biological significance of genomic loci associated with the rare markers is yet to be determined. Finally, with the aim to simplify the use of DArTFest arrays to characterize Festuca × Lolium hybrids, various bulking strategies were compared. While all bulks were suitable for identification of hybrids, only bulks of few plants have been found to reveal the rare markers.
Keywords: chiméra; fyzikální mapování chromozomů; Crops, Agricultural; Genome, Plant; genom rostlinný; genetická variace; Genotype; Sequence Analysis, DNA; sekvenční analýza DNA; zemědělské plodiny; chromozomy rostlin; Oligonucleotide Array Sequence Analysis; Chromosomes, Plant; genetické markery; DNA rostlinná; DNA, Plant; Physical Chromosome Mapping; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Festuca; Lolium; Hybridization, Genetic; Chimera; jílek; genotyp; hybridizace genetická; Genetic Variation; Genetic Markers